Employee Insights on Workforce Diversity and Job Performance in Nepalese Public Enterprises - Shrestha, Prakash; Bhujel, Sana Babu (Kshitiz Management Review, 2025)
This study explores how workforce diversity influences employee performance in Nepalese public enterprises. Using descriptive and explanatory research methods, it examines diversity traits and their effect on job performance. A stratified random sample of 200 respondents from four public enterprises was selected, with 50 self-administered questionnaires distributed in each. Findings indicate that employees perceive significant demographic diversity, with relatively less diversity in educational and professional backgrounds but notable socioeconomic diversity. Diverse regional representation enhances cultural inclusion, contributing positively to workforce dynamics and job performance. The study concludes that workforce diversity positively affects job performance, with socioeconomic diversity showing the strongest impact. Employees from varied economic backgrounds significantly enhance workplace success. Demographic diversity, including age, gender, and ethnicity, along with geographic diversity, also positively influence job performance. However, diversity in educational qualifications and professional experience shows a weaker effect, indicating that these traits may not be as critical as others in influencing job performance. This research highlights the importance of embracing workforce diversity to optimize employee performance and organizational success.